Indications, outcomes and complications of therapeutic endoscopic retrograde cholangiopancreatography procedures in a tertiary care centre in North East India - Choudhury, Bikash Narayan; Deka, Utpal Jyoti; Baruah, Bhaskar Jyoti; Bhattachayya, Mallika; Sarma, Preeti; Debroy, Porag (International Journal of Research in Medical Sciences, 2020)
Background: Therapeutic endoscopic retrograde cholangiopancreatography (ERCP) is one of the most complex endoscopic procedures in the management of several pancreatobiliary diseases. There is no comprehensive data available till date about ERCP procedures from North East India. The aim of this study was to review the indications, outcomes and complications of endoscopic retrograde cholangiopancreatography (ERCP) procedures in a tertiary care centre of North East India. Methods: We retrospectively analysed the clinical records of all patients undergoing ERCP between July 2011 and November 2019. ERCP was performed under sedation (Midazolam + Pentazocine). Patient’s demographic characters, ERCP indications, outcome and post-ERCP complications were reviewed. Potential important patient and procedure related risk factors for overall post-ERCP complications were investigated. Results: A total 1038 patients were included in the study. Cannulation of the desired duct was successful in 89.2% of ERCPs. Among them male patients were 392 and females were 646. Mean age was 45 years and the age range were 7 to 92 years. Commonest indication was choledocholithiasis followed by malignancy. Overall Success rate was 82.66% with 84.64% in CBD stone and 75.65% in stenting of malignancy. Post ERCP complications developed in 96 patients (9.2%) and pancreatitis was the most common post-ERCP complication. Sedation related complications occurred only in few cases. Conclusions: Despite its associated morbidity and risk of mortality, ERCP is an important method for managing the pancreatic-biliary diseases. Indications, outcomes, and complications of therapeutic ERCPs in our centre are comparable to those reported from other centres.